Molecular Mechanisms of Colistin Resistance in Klebsiella pneumoniae in a Tertiary Care Teaching Hospital - Liu, Yanling; Lin, Yiqing; Wang, Ziwen; Hu, Niya; Liu, Qiong; Zhou, Wenkai; Li, Xiuzhen; Hu, Longhua; Guo, Jian; Huang, Xiaotian; Zeng, Lingbing (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Over the last two decades, the prevalence of colistin resistance among the members of Enterobacteriaceae has been increasing, particularly, among Klebsiella pneumoniae isolates; this limits the potential use of colistin and leads to worsened clinical outcomes. Methods: We investigated the prevalence and genetic characteristics of colistin-resistant K. pneumoniae (COLR-KP) in clinical isolates using genomic sequencing. Results: In total, 53 K. pneumoniae isolates (4.5%, 53/1,171) were confirmed as COLR-KP, of which eight carried mobile colistin-resistant (mcr) gene. Although the overall prevalence rate (0.7%, 8/1,171) of mcr-like genes in clinical K. pneumoniae remained relatively low, the presence of mcr (15.1%, 8/53) among the COLR-KP isolates indicated that the mobile resistance gene was already widespread among K. pneumoniae isolates in the hospital setting. We randomly selected 13 COLR-KP isolates (four mcr-bearing and nine non-mcr-bearing isolates) for whole-genome sequencing, including two pandrug-resistant and four sequence type (ST) 11 isolates. Phylogenetic analysis revealed that all COLR-KP isolates were genetically diverse. Among the four mcr-bearing isolates, three (KP4, KP18, and KP30) were positive for mcr-1 and one (KP23) for mcr-8; none of the other mcr genes were detected. The mcr-1 in the KP4 and KP30 isolates located in an IncX4 plasmid (approximately 33 kb) and could be successfully transferred to Escherichia coli J53AZR. In contrast, for the mcr-8-bearing plasmid in KP23 (IncFII), colistin resistance could not be transferred by conjugation. A novel plasmid bearing an acquired tigecycline-resistance gene, tmexCD1-toprJ1, coexisted in the mcr-1-bearing isolate KP18. The most common chromosomal mutation associated with colistin resistance was a T246A amino acid substitution in PmrB, which was identified in most COLR-KP isolates (11/13, 84.6%). All ST11 isolates additionally had an R256G amino acid substitution. Critical virulence factors associated with hypervirulent K. pneumoniae were detected in the four COLR-KP isolates; these virulence factors included aerobactin, salmochelin, and yersiniabactin. Conclusion: We found that mcr-bearing COLR-KP emerged in our hospital and was growing at an increasing rate. Simultaneous emergence of hypervirulence and colistin-tigecycline-carbapenem resistance in the epidemic clone ST11 K. pneumoniae was also observed; this highlights the significance of active and continuous surveillance.